Kampanye Infak di Media Sosial dan Niat Perilaku Infak Masyarakat Saat Pandemi Covid-19 - Muhammad Khaerul Muttaqien; Tajudin Mas’ud (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
The development of donation collection and public donation behavior has been increasingly visible since the Covid 19 outbreak spread to various countries in the world, including Indonesia. Optimizing the use of social media for the zakat infaq alms campaign and the use of electronic services for paying zakat infaq alms are two phenomena that occurred during the Covid-19 pandemic. The focus of this research is on the determinants of infaq behavior during the Covid-19 pandemic, especially the intention of the Indonesian Muslim community in paying infaq through fundraisers who carry out infaq campaigns on social media. For this reason, the variables of trust in infaq fundraisers who carry out infaq campaigns on social media and attitudes towards online infaq and social media features are used to test their intention to pay infaq. All of these variables were tested using primary data from questionnaires distributed to social media users who are Muslim and live in the DKI Jakarta, Bogor and South Tangerang areas. The PLS SEM analysis technique was used in this study to assess the measurement model, structural model and its predictive relevance. The results showed that trust in infaq fundraisers and attitudes towards online infaq as well as social media features used by infaq fundraisers had a significant effect on their intention to pay infaq through infaq fundraisers who carried out social solidarity campaigns on social media during the Covid-19 pandemic.